2007
DOI: 10.1080/10428190601059829
|View full text |Cite
|
Sign up to set email alerts
|

17p Deletion is associated with resistance of B-cell chronic lymphocytic leukemia cells to in vitro fludarabine-induced apoptosis

Abstract: We explored the relationship between the cytogenetic/biologic characteristics of B-chronic lymphocytic leukemia (B-CLL) cells and their tendency to undergo spontaneous or fludarabine-induced apoptosis in vitro. B cells from 36 B-CLL patients were incubated with or without fludarabine for 48 h. Apoptosis was determined by two assays: annexin V staining and DNA staining. Fluorescence in situ hybridization was used for detection of trisomy 12, 11q deletion, and 17p deletion. Bcl-2 and CD38 expressions were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 42 publications
1
20
0
1
Order By: Relevance
“…There was a trend to higher resistance to fludarabine in del(17p) cases [consistent with Turgut et al (27)] and to both drugs for the types A and B p53 dysfunctional samples, in line with Sturm et al (28), who found increased resistance to fludarabine and chlorambucil in cases with p53 mutations.…”
Section: Discussionsupporting
confidence: 77%
“…There was a trend to higher resistance to fludarabine in del(17p) cases [consistent with Turgut et al (27)] and to both drugs for the types A and B p53 dysfunctional samples, in line with Sturm et al (28), who found increased resistance to fludarabine and chlorambucil in cases with p53 mutations.…”
Section: Discussionsupporting
confidence: 77%
“…4B). Del17p results in loss of expression of p53 and is associated with short survival time and resistance to purine analogues, such as fludarabine (30,31). The three samples with del17p were assessed for fludarabine-and PBOX-15-induced apoptosis after 24 hour treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] Therefore, new agents capable of effectively killing p53-null CLL cells would have significant clinical impact. Among 30 CLL samples tested for genetic abnormalities, 7 samples had deletion of 17p.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In particular, CLL cells with unfavorable cytogenetic alterations such as deletion of chromosome 17p with loss of p53 are often resistant to fludarabine and cyclophosphamide. 4,5 Similarly, CLL cells from patients in advanced disease stages or with a history of prior chemotherapy exhibit elevated oxidative stress, 6 and thus may have a greater potential to acquire additional mutations and genetic abnormalities, leading to drug resistance and disease progression. This presents a significant challenge in treatment of CLL.…”
Section: Introductionmentioning
confidence: 99%